Phase I Dose Escalation of Doxorubicin Chemotherapy in Tumor‐Bearing Equidae. (26th July 2013) - Théon, A.P.; Pusterla, N.; Magdesian, K.G.; Wilson, W.D.
Abstract : Background: There is no information on the use of doxorubicin in horses with tumors. Objective: To determine dose‐limiting toxicosis (DLT) and maximum tolerated dose (MTD) of doxorubicin in tumor‐bearing horses. Animals: Seventeen horses with 34 localized or multicentric advanced tumors. Methods: Two‐stage dose‐ranging design involving intrapatient and interpatient dose escalation. Treatment protocol included 6 treatment cycles given at 3‐week intervals with dosages ranging from 40 to 85 mg/m 2 . Clinical signs, hematologic, and nonhematologic changes were evaluated. Results: Total doses ranged from 1, 127 to 2, 900 mg in 12 horses that completed the assigned treatment protocols. The MTD was 75 mg/m 2 . Hypersensitivity reactions and neutropenia were dose limiting. Hypersensitivity was dose‐dependent but schedule invariant. Neutropenia was dose‐ and cycle‐dependent but dose‐escalation schedule invariant. Cardiotoxicity was not observed. Conclusion and Clinical Relevance: The recommended dosage of doxorubicin to treat horses is 70 mg/m 2 given at 3‐week intervals as single agent. Adjunctive treatment with antihistamines and nonsteroidal anti‐inflammatory drugs is recommended to control hypersensitivity.